Genetic characterization of silkworm (Bombyx mori L.) strains (Lepidoptera: Bombicidae) with different geographical origin on the basis of isozyme markers - Teodora Atanasova Staykova; Panomir Ivanov Tzenov; Yolanda Bogdanova Vasileva; Sibel Djevdet Aziz; Evgenya Neshova Ivanova; Ivan Iordanov Stoyanov; Penka Lazarova Vasileva; Teodora Petrova Popova (Acta Scientiarum. Biological Sciences, 2020)
The aim of the present study was to assess genetics variations within and among strains with different geographical origin, belonging to Bulgarian germplasm bank of mulberry silkworm (Bombyx mori L.) and to establish their relationships using isoenzyme markers. Polyacrilamide gel electrophoresis (PAGE) was used to study the isoenzymes of nonspecific esterases (EST), malate dehydrogenase (MDH) and acid phosphatase (ACP) from haemolymph, phosphoglucomutase (PGM) and hexokinase (HK) from silk glands and alkaline phosphatase (ALP) from midgut of mulberry silkworm (Bombyx mori L.). Variability was evident in all of these enzyme systems among twelve strains from Bulgarian germplasm resources of B. mori. Total of nine loci were detected. All of them (100%) were polymorphic. “Null” alleles in four loci were determined. Intra- and inter-strain polymorphism was obtained. The degree of polymorphism ranged from 0% to 77.80%. Low levels of observed heterozygosity in comparison with the expected one have been calculated in almost all of strains as well as deviations from Hardy-Weinberg equilibrium in almost all analyzed loci, resulting of excess of homozygotes. The value of FST was 0.4903. The dendrogram constructed with the values of genetic distance manifests that Romanian strain Cislau Tokay is formed one main clade while the rest strains studied (from Bulgaria, Japan, China, Vietnam, Spain, Syria and Egypt) are formed the other clade with subclades. The genetic data of the tested strains from different geographical regions, would be used for identifying suitable parents for breeding programs with a view to yield improvement in this species with economic significance.